Securing cyberspace : a new domain for national security - Burns, R. Nicholas, 1956-; Price, Jonathon; Nye, Joseph S.; Scowcroft, Brent (Aspen Institute, 2012)
This book is a collection of papers commissioned for the 2011 Aspen Strategy Group workshop, a bipartisan meeting of top national security experts. The papers examine the complexities of the emerging cyber threat, as well as the possibilities -- and inherent challenges -- of crafting effective domestic and international cyber policy. Authors explore topics such as the economic impact of cyber crime, cyber as a new dimension of warfare, the revolutionary potential of internet freedom, and the future realities the United States will face in the new age of heightened internet connectivity.